2019
DOI: 10.3126/jkmc.v8i2.28166
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke: Observations and analysis of stroke patients admitted in a tertiary hospital of Kathmandu

Abstract: Background: Stroke is a disabling condition that has physical and mental impact on a patient’s life. Stroke is an important morbidity for low and middle income countries like Nepal. Hypertension, diabetes, smoking, and dyslipidemia are common risk factors in this regard and are inadequately controlled; mainly because of poor public awareness, inadequate infrastructure, lack of service and qualified manpower.Objectives: This study aims to provide insight into the epidemiology and risk factors in ischemic stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…This finding was supported by study done in our country which show that dyslipidemia was present in 77.2%. 4 Similarly, a study done in Nigeria showed an incidence of dyslipidemia was 92.30% which is significantly higher as compared to our study. 13 This may support that, a study done in our country states that the high dominance of dyslipidemia could be due to the sedentary lifestyle and environment changes among Nepalese patients and found a three-fold rise in the incidence of dyslipidemia in stroke patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…This finding was supported by study done in our country which show that dyslipidemia was present in 77.2%. 4 Similarly, a study done in Nigeria showed an incidence of dyslipidemia was 92.30% which is significantly higher as compared to our study. 13 This may support that, a study done in our country states that the high dominance of dyslipidemia could be due to the sedentary lifestyle and environment changes among Nepalese patients and found a three-fold rise in the incidence of dyslipidemia in stroke patients.…”
Section: Discussionsupporting
confidence: 46%
“… 2 Population aged 60 or over is rising faster than young age group worldwide. 3 , 4 Reports have suggested that about 80% strokes occurred in individuals aged >65 years, among which 50% were aged ≥70 years and nearly 25% aged >85 years. 5 However one third of strokes occur in persons younger than 65 years.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 69.10% of respondents of this study was male, and it showed male predominance than female in ischaemic stroke and almost two-thirds of patients are above the age of 50. Beg et al (2015) found in India that the number of males is greater than that of female, Bhowmik et al (2016) found 67.7% in Bangladesh, Shakya et al (2019) found 51.1% in Nepal. The finding is also similar in developed countries.…”
Section: Discussionmentioning
confidence: 95%
“…A study done by Cotter et al (2011) found that the mean age was 63.2, and another study of 679 patients done by Bhowmik et al (2016) found the mean age to be 60.4 years. In Nepal, Shakya et al (2019) conducted a study where the mean age was 63.2 years. However, in Europe, Caso et al (2010) found the mean age as 72.68 (±13.27).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 2450 patients done by Bouzidi and associates17 found mean age was 63.2, and another of 679 patients done by Bhowmik NB et al13 found 60.4 years. In Nepal mean age was 63.2 years done by Shakya D and associates14 . However in Europe Caso V et al15 found mean age as 72.68(±13.27).This study finds large artery atherosclerosis (LAA) is the most common sub type as 43.67% (n=385).…”
mentioning
confidence: 99%